Arsitektur Efisien sebagai Pendekatan Berkelanjutan dan Finansial pada Perancangan Unit Perumahan Berskala Kecil - Paryoko, Vijar Galax Putra Jagat; Zakariya, Afif Fajar (Arsir, 2023)
House is a basic need for the whole community, but most of them are poorly provided on quantity and quality to be inhabited.  Housing developers commonly facing constraints regarding financial aspect, especially for lower middle class community housing development. Housing’s quality is decreasing, eventhough houses are playing more important role nowadays in term of sustainability development, health, and productivity support of the occupants. The role is more needed especially during and after the Covid-19 pandemic. The aims of this study is to get various strategies that can be conducted during housing design and planning phase based on efficiency of sustainability, without sacrificing the needs of today’s residents. The main method used is case study of real housing development project, starting by literature review, then analyzing the efficiency of house planning stage by developer. The success rate of efficient design strategies is measured by comparing the volume and or cost of product on each planning stage. Concluded by this study that efficient related to finance and ecological sustainability can be achieved by using strategies of collaboration of commercial discipline on architectural design phase, façade’s components reduction, synergy of façade and construction management, and triangle integration of architecture’s components, which are form, space, and structure.